Performance of a Coagulant-Membrane Bioreactor for the Removal of Dissolved Organic Matter and Phosphorus - Lee, Jung-Yeol; Choi, Bo-Kyung; Maeng, Sung Kyu; Ahn, Kyu-Hong; Song, Kyung-Guen (SOC CHEMICAL ENG JAPAN, 2013)
We report an investigation into the effectiveness of a hybrid membrane bioreactor (MBR) composed of an anoxic, non-woven fabric filter (NWFF)-aerobic reactor and an integrative micro filter (MF) with simultaneous dosing of a coagulant. Preliminary jar tests were conducted with four different additives (aluminum sulfate, FeCl3, FeSO4, and PACl) to observe the effects induced by changes in pH, alkalinity, soluble chemical oxygen demand (SCOD), and PO43-P of the permeate on the NWFF-aerobic reactor. The use of aluminum sulfate improved performance as it related to SCOD and phosphorus removal in the amounts of 2.1 mol aluminum sulfate/mol PO43-P. In the hybrid MBR, the average total phosphorus removal efficiency of the entire system was as high as 79% with continuous addition of 100 mg/L aluminum sulfate. Three-dimensional fluorescence excitation-emission matrix (F-EEM) spectroscopy of the liquid samples from the MBR indicated the presence of humic-like organic matter, which was regarded as primary aromatic organics.
Keywords: FORMING DYNAMIC MEMBRANE; 3-DIMENSIONAL EXCITATION; ACTIVATED-SLUDGE; FOULING REDUCER; FILTRATION; SYSTEM; CAKE; PRODUCTS; EFFLUENT; MBRS